Festivals and Decorations on the Occasion of the End of the Third Carlist War: The Arch of the Major Street, Liturgy, Functions and Iconography - Fernández Paradas, Antonio Rafael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
On the occasion of the end of the Third Carlist War and the entry of Alfonso XII into Madrid on March 20, 1876, the main city of the Kingdom experienced three great days of festivities, articulated in a complex program of events. By the time of the greatest event, a good number of ephemeral architectures were built in the city. Among them, the Arch financed by the Municipal Corporation stands out on Calle Mayor. The objective of this research is to offer a holistic vision of this architecture, focusing on the liturgy that developed into it and its constructive and iconographic aspects.